Erbil residents' daily consumption of heavy metals via sewage and well water-irrigated veggies - Abdulqader M. Younis; Dlshad A. Darwesh (Zanco Journal of Pure and Applied Sciences, 2023)
In Erbil city the farmers used both wastewater and well water for irrigation pupose. An inductively coupled plasma ICP was used to analyze heavy metals., including silver (Ag), aluminum (Al), iron (Fe), manganese (Mn), nickel (Ni), lead (Pb), zinc (Zn), chrome (Cr), cadmium (Cd), and arsenic (As), in wastewater, well water, agricultural soils, and vegetables (Chard, Celery, Arugula, Leek and Dill), as well as the health risks they pose in Erbil. Bio-concentration factor (BCF), daily intake (DI), Target Hazard Quotient (THQ), and carcinogenic risks (CR) were calculated to determine health concerns. Overall, metals were found in water, soil, and vegetables. The following is a rundown of the tendencies in these metals' Ni<Ag < Zn < Cr < Mn < Cd < As < Fe < Al < Pb, in the wastewater and well water and As<Ag <Cr< Fe< Cd< Ni< Zn< Mn< Al< Pb in the soil. In the vegetable samples, the mean values mg kg-1 varied from 0.74-13.90, 12.90- 41.70, 2.59- 30.40, 573–1810, 93–292, 2.44 –31.65, 23.10–116, 138–448, 13.70- 40.13 and 1.55 to 14.91, for As, Cd, Cr, Al, Pb, Ni, Mn, Fe, Zn, Ag, respectively, Cd, Pb, and Mn in chard, Arugula, and celery irrigated with wastewater and well water exceeded WHO/FAW adult safe limits. As, Cd, and Pb THQs were larger than unity in all veggies except sites 2 and 4 for As. Al in sites 1,4,6, and Mn in all sites from Chard plants had THQs > 1. As, Cd, and Cr's CR values above 10-4. These results show that local farmers' habit of irrigating vegetables with untreated wastewater and well water has generated heavy metal deposition in the soils, which is absorbed by vegetables and poses a health concern to the local people.